Probing impaired neurogenesis in human brain organoids exposed to alcohol. Issue 12 (23rd November 2017) - Zhu, Yujuan; Wang, Li; Yin, Fangchao; Yu, Yue; Wang, Yaqing; Shepard, Matthew J.; Zhuang, Zhengping; Qin, Jianhua
Abstract : The fetal brain is highly vulnerable to ethanol exposure, which can trigger various long-term neuronal disabilities and cognitive dysfunctions. Abstract : The fetal brain is highly vulnerable to ethanol exposure, which can trigger various long-term neuronal disabilities and cognitive dysfunctions. However, a comprehensive understanding of fetal brain development under ethanol exposure is challenging due to the limitations of animal models. Here, we propose a human induced pluripotent stem cell (hiPSC)-based 3D brain organoid model, and explore the mechanisms underlying neural dysfunctions in prenatal alcohol exposure (PAE) in vitro . Brain organoids were examined to resemble brain organogenesis in vivo at early stages during gestation, with specific features of neuronal differentiation, brain regionalization, and cortical organization. With ethanol exposure, the brain organoids displayed attenuated neurite outgrowth and skewed neural maturation. Transcriptome analysis identified a series of new markedly altered genes and enriched pathways, such as GSX2, RSPO2, and the Hippo signaling pathway. These genes or pathways, to our knowledge, were reported to be involved in ethanol-induced impaired neurogenesis for the first time. Our new findings might facilitate better understanding of the various postnatal neural disorders observed in individuals with PAE.